PENGARUH PENGGUNAAN BAHAN AJAR FISIKA BERBASIS KECAKAPAN KEJURUAN (VOCATIONAL SKILLS) TERHADAP HASIL BELAJAR SISWA SMK KELAS X - Lutfi Rosyidah; Ernawati Saptaningrum; Susilawati Susilawati (Jurnal Penelitian Pembelajaran Fisika, 2015)
This study aimed to determine the influence of the use of teaching materials there any physics-based vocational skills (vocational skills) to the learning outcomes of students of SMK class X.The research design was quasi-experimental design by type posttest only control design. The subjects were all students of class X Light Vehicle Engineering department SMK Negeri 5 Semarang, amounting to 104 students.Samples were taken by cluster random sampling is a class X TKR 3 as the experimental class amounting to 32 students and class X TKR 2 as the control classamounting to 36 students. This research is motivated by the lack of physics learning outcomes for disadvantaged students to connect between what is learned in how to apply,students' understanding of the concept of matter less, because there is strong knowledge and the uses of instructional materials as a source of learning in the learning process. The results of calculations based on the t-test analysis was obtained tcount> ttable ie 2.93> 1.67 with a significance level of 5% and df = 66. Because tcount> ttable then H0 rejected and Ha accepted.